Chrysis vanlithi Linsenmaier 1959 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
50. Chrysis vanlithi Linsenmaier, 1959 Chrysis rutiliventris vanlithi Linsenmaier 1959: 153. Holotype ♀; Switzerland: Wallis (NMLS) (examined). Rosa & Soon 2012 [partially erroneous records]. Chrysis rutiliventris [nec Abeille de Perrin, 1879]: Erlandsson 1971: 88 [partially erroneous records], Soon 2004: 46 [partially erroneous records]. Chrysis vanlithi : Dyntaxa 2013, Soon et al. 2014: 319. Material examined. Denmark: NWJ : Thy, Lyngby, 21.VI.1953, 1 ♀ (Ardö). Norway: AK : Baerum, Løkkåsen, 30.V–25.VI.2006, 1 ♀ (O. Hanssen); Ø : Hvaler, Skipstadkilen, 6.VI.2013, 1 ♀ (F. Ødegaard); TEY : Bamble, Langøya, 24.VI–30.VII 2009, 1 ♀ (BioFokus); VAY : Kristiansand, Bestemorsmed, 7.VI.2013, 1 ♂ (F. Strømmen); Kristiansand, Risleviga, 24.VI.2013, 1 ♂ (F. Strømmen). Sweden: Sk : Helsingborg, 1915, 1 ♀; Ystad, 1916, 1 ♀. Distribution. Denmark, Norway, Sweden.—Westpalearctic: from central and northern Europe to Southwest Asia (Linsenmaier 1997). Remarks. This species has been reported from all the Nordic and Baltic countries except Estonia, though most published records have turned out to be based on misidentified specimens. So far, only two specimens collected from southern Sweden and five specimens from southern Norway have proven to belong to this species (see data above). Also one specimen from northwestern Denmark is known, which was determined by Linsenmaier and is preserved in Linsenmaier’s collection in NMLS (see data above). The determinations of the Norwegian specimens were confirmed by comparing their DNA barcodes with a barcode of a Swiss specimen determined by Linsenmaier (Soon et al . 2014). The species seems to have a western distribution in northern Europe. It has been found in northern Germany, Schleswig-Holstein (Smissen 2010c), and according to Morgan (1984), it is widespread in the British Isles. The species was reported from Finland by Silfverberg (1981: 61, as C. rutiliventris [erroneously based on Erlandson 1971: 88]), Vikberg (1986b: 68, as C. rutiliventris ) and Söderman & Vikberg (2002: 45, as C. rutiliventris vanlithi ). All Finnish specimens in collections have been found to belong to other species (e.g. C. schencki ). The records from Latvia (Soon 2004: 46, as C. rutiliventris ) and Lithuania (Rosa & Soon 2012, as C. rutiliventris rutiliventris ) as well as some records from Sweden (e.g. Hallin 2009, 2012, as C. rutiliventris ) are also likely to be erroneous. The taxon was reported from Norway by Strumia & Berg (1995, as C. rutiliventris ), and later it was listed by Artsdatabanken (2010, as C. rutiliventris ) and Rosa & Soon (2012, as C. rutiliventris ). These records were also based on misidentified specimens. Linsenmaier (1959) described C. vanlithi as a subspecies of C. rutiliventris . According to the description, it differs from the nominotypical subspecies in its larger size, shorter anal rim and less even punctation on the second tergite (posteriorly sparser and anteriorly coarser). It was also reported to occur in central and northern Europe, whereas C. rutiliventris sensu stricto is mainly restricted to the south. Linsenmaier (1997) already suggested that ssp. vanlithi could be a separate species. In fact, mitochondrial DNA studies, and the coexistence of vanlithi and the nominotypical subspecies in central Europe support their classification as separate species (Rosa 2006, Soon et al. 2014). C. vanlithi was listed as a separate species in the Swedish taxonomic database (Dyntaxa 2013), and we have also considered it as a distinct species. Linsenmaier (1997) placed C. rutiliventris and C. ruddii to his “ ruddii - Aspekt” of the Chrysis ignita group, which is characterized by a short and broad pronotum, relatively dense punctation of the second tergite, and long, dense pubescense. According to molecular studies, C. vanlithi is not closely related to C. rutiliventris but belongs to the Chrysis comta subgroup sensu Soon & Saarma (2011). The holotype of C. vanlithi , which is deposited in Linsenmaier’s collection in NMLS, morphologically resembles the Swiss and Norwegian specimens included in the DNA study (Soon et al . 2014). Thus the attribution of the name C. vanlithi to Nordic species is supported, although more detailed studies are still needed. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on pages 36-37, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Brucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32, 1 - 232.", "Rosa, P. & Soon, V. (2012) Fauna Europaea: Chrysididae. In: Mitroiu, M. - D. (Ed.), Fauna Europaea: Hymenoptera, version 2. 5. Available from http: // www. faunaeur. org (accessed 1 November 2013)", "Erlandsson, S. (1971) Catalogus Insectorum Sueciae XIX. Hymenoptera: Aculeata. Entomologisk Tidskrift, 22, 87 - 94.", "Soon, V. (2004) Eesti kuldherilased (Hymenoptera, Apocrita, Chrysididae). Master's thesis, University of Tartu. 81 pp. Available from: http: // dspace. utlib. ee / dspace / bitstream / handle / 10062 / 1236 / Soon. pdf; jsessionid = 6617 B 92 C 3 E 468623 BC 1 5 CAC 1 E 8 B 95 C 67? sequence = 5 (accessed 1 November 2013)", "Dyntaxa (2013) Svensk Taxonomisk Databas - Swedish Taxonomic Database (version 1.1.5059.20729). Available from: http: / / www. dyntaxa. se / (accessed 1 November 2013)", "Soon, V., Budrys, E., Orlovskyte, S., Paukkunen, J., Odegaard, F., Ljubomirov, T. & Saarma, U. (2014) Testing the validity of Northern European species in the Chrysis ignita species group (Hymenoptera: Chrysididae) with DNA Barcoding. Zootaxa, 3786 (3), 301 - 330. http: // dx. doi. org / 10.11646 / zootaxa. 3786.3.4", "Linsenmaier, W. (1997) Die Goldwespen der Schweiz. Veroffentlichungen aus dem Natur-Museum Luzern, 9, 1 - 139.", "Smissen, J. van der (2010 c) Anschliessender Beitrag zur Stechimmenfauna des mittleren und sudlichen Schleswig-Holstein, angrenzender Gebiete in Mecklenburg und Niedersachsen sowie einige Nachweise au sanderen Bundeslandern (Hymenoptera Aculeata: Apidae, Chrysididae, \" Scolioidea \", Vespidae, Pompilidae, Sphecidae; Hymenoptera Symphyta: Xiphydriidae, Trigonalyidae). Verhandlungen des Vereins fur Naturwissenschaftliche Heimatforschung zu Hamburg e. V., 43, 255 - 354.", "Morgan, D. (1984) Cuckoo-wasps, Hymenoptera, Chrysididae. Handbooks for the Identification of British Insects, Vol. 6, Part 5, Royal Entomological Society of London, London, 37 pp.", "Silfverberg, H. (1981) Additions to the Finnish insect fauna during the years 1976 - 1980. Notulae Entomolgicae, 61, 45 - 61.", "Vikberg, V. (1986 b) A checklist of aculeate Hymenoptera of Finland (Hymenoptera, Apocrita Aculeata). Notulae Entomologicae, 66, 65 - 85.", "Hallin, G. (2009) Gaddsteklar fran Blekinge 1984 - 2007. Sammanstallning av gjorda fynd. Lansstyrelsen i Blekinge lan, Rapport nr 2009: 8, 46 pp.", "Hallin, G. (2012) Gaddsteklar i Orebro lan - 60 ars eget samlande och en sammanstallning av befintlig kunskap. Lansstyrelsen i Orebro lan, Publ. Nr 2012: 39, 73 pp.", "Strumia, F. & Berg, O. (1995) Three gold wasps new to Norway. Fauna norvegica, Series B, 42, 64 - 65.", "Artsdatabanken (2010) Nasjonal kunnskapskilde for biologisk mangfold [Database of Norway's fauna and flora.] Available from: http: // www. artsportalen. artsdatabanken. no / (accessed 1 November 2013)", "Rosa, P. (2006) I Crisidi della Valle d'Aosta (Hymenoptera, Chrysididae). Monografie del Museo Regionale di Scienze Naturali, 6, St. - Pierre, Aosta, 368 pp., xvi + 32 pls.", "Soon, V. & Saarma, U. (2011) Mitochondrial phylogeny of the Chrysis ignita (Hymenoptera: Chrysididae) species group based on simultaneous Bayesian alignment and phylogeny reconstruction. Molecular Phylogenetics and Evolution, 60, 13 - 20. http: // dx. doi. org / 10.1016 / j. ympev. 2011.04.005"]}